Literature Review: Physical Activity, Diet, and Socioeconomics on Obesity in Elementary Schools - Aji, Tegar Laras Pandu; Sulistiono, Sulistiono; Harmono, Setyo (Journal Coaching Education Sports, 2023)
The global obesity rate has doubled since 1980, leading to widespread health concerns. This study analyzes the relationships between physical activity, dietary patterns, and socioeconomic status on obesity in elementary school children. Based on a review of 11 national and international articles published between 2016 and 2020, the study finds that factors contributing to childhood obesity include sedentary behavior, poor dietary habits, genetic predisposition, and environmental influences. Results suggest a strong correlation between reduced physical activity and increased obesity risk, along with a connection between unhealthy dietary patterns and the prevalence of obesity. Additionally, the study highlights the influence of socioeconomic factors on dietary choices, particularly in the context of the availability and affordability of fast food. These findings emphasize the need for comprehensive interventions and awareness campaigns to promote healthy lifestyles and prevent childhood obesity.